1960
DOI: 10.1002/zaac.19603060113
|View full text |Cite
|
Sign up to set email alerts
|

Über die Darstellung höherer β‐Diketonkomplexe des Eisens, Rutheniums und Rhodiums

Abstract: Darstellung und Eigenschaften der noch nicht bekannten Innerkomplexe des Eisens, Rutheniums und Rhodiums mit Dibenzoylmethan bzw. p,p′‐Dinitro‐dibenzoylmethan werden beschrieben. Die früher1) bei Diketonkomplexen erfolglos versuchte Methode des Chelataustauschs wurde zu einem sehr allgemein anwendbaren Verfahren zur Darstellung schwer zugänglicher bzw. nach den bisherigen Methoden unzugänglicher höhere β‐Diketonkomplexe, welches auf dem Diketonaustausch der einfachen Metall‐Acetylacetonate beruht, entwickel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

1964
1964
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 6 publications
0
4
0
3
Order By: Relevance
“…The second category of ruthenium precursor complexes are ruthenium-b-diketonates or Ru(CO) 2 (b-diketonates) 2 . 92 Simple complexes of type [Ru(acac) 3 ] 4, acac ¼ acetylacetonatemonoanion (brown colour) were prepared by Wolf et al 93 A modi-ed procedure by Rose et al was also exploited to prepare ruthenium complexes. 94 Its thermal properties for the preparation of RuO 2 lms by CVD was studied by Bykov et al 95 (see also Table 1) The complex and its triuorinated derivative were found as prospective precursors in CVD for the preparation of RuO 2 and Ru lms.…”
Section: Different Classes Of Ruthenium Complexes Used As Cvd Precursorsmentioning
confidence: 99%
“…The second category of ruthenium precursor complexes are ruthenium-b-diketonates or Ru(CO) 2 (b-diketonates) 2 . 92 Simple complexes of type [Ru(acac) 3 ] 4, acac ¼ acetylacetonatemonoanion (brown colour) were prepared by Wolf et al 93 A modi-ed procedure by Rose et al was also exploited to prepare ruthenium complexes. 94 Its thermal properties for the preparation of RuO 2 lms by CVD was studied by Bykov et al 95 (see also Table 1) The complex and its triuorinated derivative were found as prospective precursors in CVD for the preparation of RuO 2 and Ru lms.…”
Section: Different Classes Of Ruthenium Complexes Used As Cvd Precursorsmentioning
confidence: 99%
“…Tris(ß-diketone) complexes of dibenzoylmethane and /?,/? '-dinitrodibenzoylmethane have been prepared by heating Rh(acac)3 with the ß-diketone in a high-boiling solvent 287 . The tropolone complex Rh(C 7 H 5 0 2 )3 has been described 288 .…”
Section: Complexes Of Oxygen Ligandsmentioning
confidence: 99%
“…Pokrovno staklo (Gold Seal, SAD) (8,154). Cistoca kompleksa odredjena је mjkroanaljzom ј spektrofotometrijskom analizom.…”
Section: 1 P Ostupak Pr/preme Preparata Cel/ja Za Anal/zu Fluorescentn/m Mikroskopomunclassified
“…З. Kako је glavnj cjlj delovanja antitumorskih agenasa zapravo uvodenje maligne celije u apoptozu, ucesce kaspaza u mehanizmu aktivacije apoptoze opisano је u poglavlju 2. 4. s obzirom na postojanje sirokog potencijala antitumorskog dejstva nestandardnjh kompleksa metala kao sto su transizomerj platjne ј derivatj prelaznjh metala, cjlj ovog rada Ьiо је poredenje aktivnosti cjsplatine sa aktivnoscu cis-/transgeometrijskih izomera djpjrjdjndjhloroplatjne(ll), [Pt(Py)2CI2] 13-djketonato kompleksa prelaznih metala: rutenijuma(lll), hroma(lll) i rodijuma(l ll).Sinteza ј struktura 13-diketonato kompleksa ispitjvanih u ovom radu , vec је opisana u ljteraturi(8). Na osnovu postojecjh ljteraturnih podataka koji ukazuju da neki Ьidentatni /3-diketonato kompleksi Ru(II)/Ru(з Doktorska dise,•tacija-Teorijski deo 2.…”
unclassified
See 1 more Smart Citation